Initial Influenza Virus Replication Can Be Limited in Allergic Asthma Through Rapid Induction of Type III Interferons in Respiratory Epithelium - An, Sujin; Jeon, Yung Jin; Jo, Ara; Lim, Hyun Jung; Han, Young Eun; Cho, Sung Woo; Kim, Hye Young; Kim, Hyun Jik (Frontiers in Immunology, 2018)
Although asthmatics has been considered to be highly susceptible to respiratory viral infection and most studies have focused on exacerbation of asthma by influenza A virus (IAV) infection, few experimental evidences exist to directly demonstrate that asthmatic mice are actually resistant to IAV infection. Here we show that asthmatic mice are not highly susceptible to IAV in the early stage of infection and type III interferon (IFN) maintains antiviral immune response in the lung of IAV-infected asthmatic mouse resulting in inhibition of initial viral spread. C57BL/6 Mice with allergic asthma were infected with IAV (WS/33: H1N1) and survival rate, body weight, viral titer, histopathologic findings of lung and cytokine profiles including IFNs and Th2 cytokines were measured. Notably, asthmatic mice were significantly resistant to IAV and showed lower viral load until 7 days after infection. Further, IAV-infected asthmatic mice exhibited decreased Th2-related inflammation in lung tissue until 7 days. These increased antiviral resistant mechanism and reduced Th2 inflammation were attributable to rapid induction of type III IFNs and blockade of type III IFNs in asthmatic lung led to aggravated IAV infection and to enhance the production of Th2 cytokines. Asthmatic mice showed bi-phasic responses against IAV-caused lung infection such as rapid production of type III IFNs and subsequent induction of type II IFNs. Actually, IAV-infected asthmatic mice become vulnerable to IAV infection after 7 days with noticeable morbidity and severe weight loss. However, intranasal administration of type III IFNs protects completely asthmatic mice from IAV-mediated immunopathology and lung infection until 14 days after infection. Taken together, our study indicates that the rapid induction of type III IFN might be distinctive immunologic findings in the respiratory tract of IAV-infected asthmatic mice at the early stage of infection and crucial for suppression of initial viral spread in vivo asthma accompanying with restriction of Th2 cytokine productions.